First detection and molecular characteristics of bopivirus from goats in China - Yang, Youwen; Abi, Kehamo; Li, Yanmin; Yang, Chen; Yang, Falong (Frontiers in Veterinary Science, 2022)
A metavirome analysis was performed and detected bopivirus in the diarrhoeal fecal samples of goats in China. A total of 136 fecal samples were collected from yeanlings in Sichuan province, China. Moreover, "Bopivirus B" strains were detected by a specific RT-PCR. The results showed that the overall detection rate of “Bopivirus B” was 19.12% (26/136). Additionally, there was a higher detection rate (24.05%, 19/79) in the fecal samples collected from yeanlings with diarrhoea compared to those from asymptomatic animals (12.28%, 7/57). In these samples, no other common diarrhoea-causing pathogens were detected except for three enteric viruses, namely caprine enterovirus, caprine kobuvirus and caprine hunnivirus (with detection rates of 13.97%, 13.97% and 8.82%, respectively). Subsequently, full-length VP4, VP2, VP3, and VP1 genes from "Bopivirus B"-positive samples were amplified, cloned, sequenced, and analyzed. The phylogenetic analysis performed on the VP1 genes revealed that the identified bopivirus belonged to genotype B1 (7 strains) and B2 (3 strains) and presented a high genetic diversity. Furthermore, a complete genome sequence of a "Bopivirus B" strain (SWUN/B1/2022) was obtained using PCR from fecal sample of a diarrhoeal yeanling. The complete genome was 7,309 nucleotides in length with a standard picornavirus genome organization, and shares 93.10% and 91.10% nucleotide similarity with bopivirus B1 genotype strain ovine/TB14/2010-HUN and bopivirus B2 genotype strain goat/AGK16/2020-HUN, respectively. According to the species classification criteria put forward by the International Committee on Taxonomy of Viruses and VP1 genotype, the strain SWUN/B1/2022 belongs to the bopivirus B1. This strain has unique amino acid substitutions in the VP4, VP2, VP3, and VP1 genes. Moreover, genomic recombination analysis revealed that this strain may be a minor parental strain of bopivirus B1 ovine/TB14/2010-HUN. Evolutionary analysis based on the 2C and 3CD genes revealed that the new bopivirus B1 strain SWUN/B1/2022 presents a unique evolutionary pattern. This study provided evidence to suggest that "Bopivirus B" is circulating with substantial genetic diversity in goats in China at present, and the mixed infection of "Bopivirus B" with other enteric viruses should be considered to be a composite factor in the occurrence of viral diarrhoea in goats.